Prediksi Prospek Harga Real Estate di Masa Pandemi dengan 3 Atribut Berbasis Algoritma Linear Regression - gita syafarina; Tri Wahyu Qur’ana; Galih Mahalisa (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Investment is one of the most sought after by some people even during the pandemic, various types of investments range from gold, stocks, and property to real estate. real estate (real estate) or real estate is a legal term that includes land along with anything that remains on the land, such as buildings or projects. Real estate business is a type of activity that has great potential for the long term. Therefore, many people are interested in this field, including investing. This study will process a dataset using a method to get a real estate price prediction by testing using the Linear Regression method on 3 features that affect real estate prices. the accuracy value obtained is 67.8%. Therefore, the price of real estate prospects during the pandemic does not increase or decrease in terms of selling prices